Postneurosurgical Central Nervous System Infection Due to Enterococcus faecalis Successfully Treated With Intraventricular Vancomycin. Issue 3 (May 2016) - Patel, Trisha; Lewis, Mark E.; Niesley, Michelle L.; Chowdhury, Mashiul
Abstract : Abstract: Infections from Enterococcus faecalis and Enterococcus faecium are uncommon in the post-neurosurgical intervention setting., [1, 2, 3, 4] Intraventricular antibiotics are recommended when standard intravenous therapy fails. [5] Here we present a case of post-neurosurgical ventriculitis, meningitis, and cerebritis in an oncology patient caused by refractory Enterococcus faecalis successfully treated with intraventricular vancomycin.